ISOLATION OF POLIOMYELITIS VIRUS FROM THE NASOPHARYNX - Paul, John R. (The Rockefeller University Press, 1935)
A single example of mild illness diagnosed as suspected abortive poliomyelitis is described in which the virus of poliomyelitis was recovered from the nasopharynx by three different methods. Failure to recover virus from a total of twenty-six cases diagnosed as suspected or abortive poliomyelitis and fourteen contacts is also reported. The original material from the nasopharynx of the positive case proved unusually infective for the monkey, apparently even more so than are the majority of suspensions of spinal cords from fatal human cases of poliomyelitis. An explanation of this fact is not clear. The method of isolating human virus from the throat, by means of preserving the sediment of washings from this site in glycerine, has been shown to be efficient in one case for a period of 101 days.